A Systems Dynamics Model for Mobile Industry Governance in the Context of the Kenyan Vision 2030 - Omamo, Amos O.; Rodriguez, Anthony J.; Muliaro, Joseph Wafula (International Journal of System Dynamics Applications, 2018)
This article describes how Kenya has emerged in recent times as one of the fastest-growing telecom markets in the world. This article presents a system dynamics-integrated model of the Kenyan telecommunication sector—mobile telephony—that has been developed and calibrated to demonstrate the various interactions among system variables and the resultant impact on economic growth through simulations. The simulation result proves that the regulator, the Communications Authority of Kenya, should be the key entity to be governed. This modeling process started by delineating the mobile industry's system boundary. The interactions amongst the entities were then described. Based on a historical data analysis and the system archetypes identified, a system dynamics (SD) model was developed. The research tested the results of the model in a combination of scenarios, apart from several underlying feedback effects, it was found that mobile telephony and growth in gross domestic product (GDP) had strong positive correlation.